Effects of chronic comorbidity on psychological well-being among older persons in northern Peninsular Malaysia - Momtaz, Yadollah Abolfathi; Tengku Abdul Hamid, Tengku Aizan; Yahaya, Nurizan; Ibrahim, Rahimah (Springer, 2010)
Comorbidity is found to be more prevalent among older people and increases the need for health care. This study examined the effects of chronic comorbidity on psychological well-being of elderly people. A cross-sectional, descriptive study among Northern Malaysians was conducted, involving 385 older people aged 60 years and above randomly selected through multistage random sampling. All respondents completed a questionnaire booklet containing sociodemographic characteristics, self reported chronic morbidity, and WHO-5 Well-Being Index. Findings of this study demonstrated the prevalence and the mean morbidity were 77.7% and 1.62 (SD = 1.48), respectively. The mean score for the psychological well-being was 57.96 (SD = 22.97). Results of multiple regression analysis indicated psychological well-being is negatively affected by the number of concurrent chronic conditions. The results also showed that chronic comorbidity has the most negative effect on psychological well-being. Therefore, it is important to identify mediating factors and coping strategies that might improve psychological well-being of elderly people with coexisting morbid conditions.